A solid-liquid diffusion couple for studying phase transition and diffusion kinetics of Ni-Al system, and a preparation method and application thereof

CN122979592APending Publication Date: 2026-10-27SHANGHAI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610719138.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-05-25
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0005]为了解决现有技术存在的问题,针对现有技术中难以通过单次实验高效获得Ni-Al二元体系全成分范围高温平衡相及其扩散动力学参数的问题,以及纯Ni与液态Al难以进行稳定扩散偶实验的难题,本发明提供一种高通量Ni-Al固液扩散偶及其制备与分析方法

Benefits of technology

1.高通量优势:本发明单次实验即可在Ni-Al扩散偶中形成从纯Ni到纯Al的连续成分梯度,一次性获得Ni-Al二元相图在对应温度下的全部高温平衡相,包括γ-Ni(Al)固溶体、γ′-Ni3Al、β′-NiAl(马氏体)、Ni-rich β-NiAl相和β-NiAl相,极大地提高了实验效率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122979592A_ABST
    Figure CN122979592A_ABST
Patent Text Reader

Abstract

The application discloses a solid-liquid diffusion couple and a preparation method and application thereof, relates to the field of material science, and comprises a nickel sleeve, an aluminum block encapsulated in the sleeve and nickel end covers sealed and welded at both ends of the sleeve. The nickel sleeve, the aluminum block and the nickel end covers are subjected to surface pretreatment to realize close interference fit; the nickel end covers and the sleeve are sealed and welded by electron beam welding in a vacuum environment to form a closed cavity. The encapsulated diffusion couple is subjected to annealing treatment, solid-liquid interdiffusion is realized by using the melting of aluminum, and then quenching is carried out to retain high-temperature structure. The application realizes solid-liquid contact and interdiffusion of pure nickel and pure aluminum at high temperature, can obtain a multilayer structure of all high-temperature equilibrium phases in a single experiment, can also measure key kinetic parameters such as interdiffusion coefficients, frequency factors and diffusion activation energies of each phase in a specific temperature range, is suitable for studying phase transition and diffusion kinetics of the Ni-Al system, and is used for developing nickel-aluminum-based bonding layer materials for thermal barrier coatings and analyzing failure mechanism.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the fields of materials science and engineering technology, specifically to a solid-liquid diffusion couple for studying the high-temperature phase transformation and interdiffusion kinetics of nickel-aluminum (Ni-Al) binary systems, and its preparation and analysis methods, which are particularly applicable to the study of failure mechanisms and performance optimization of Ni-Al based binder materials in thermal barrier coatings. Background Technology

[0002] Nickel-based superalloys are widely used in hot-end components of aero-engines, and are often protected by binder layers and thermal barrier coatings based on β-NiAl intermetallic compounds. The service life of the coating is highly dependent on the interdiffusion behavior and phase stability of the binder layer at high temperatures. At high temperatures, the diffusion of Al into the matrix leads to aluminum depletion in the binder layer, which may induce β → β′ martensitic phase transformation and β → γ′ transformation. The accompanying volume changes induce coating stress, ultimately leading to coating wrinkling and failure. Therefore, accurately obtaining the phase transformation law of the Ni-Al system at high temperatures and the diffusion kinetic parameters (such as diffusion coefficient and activation energy) of each constituent phase is crucial for understanding the coating failure mechanism and optimizing the composition and structure of the binder layer.

[0003] Currently, the main methods for determining the diffusion kinetics parameters of the Ni-Al system include first-principles calculations, radioisotope tracing, and diffusion couple methods. First-principles calculations have short timescales (picoseconds to nanoseconds) and small model sizes, making it difficult to reflect actual diffusion processes, and they are usually only applicable to specific compositions. Radioisotope tracing methods offer high precision, but require designing multiple sets of experiments for different compositions, resulting in high cost and low efficiency. Traditional solid-state diffusion couple methods (such as Ni / NiAl diffusion couples) typically only study phase transitions at a single interface or within a limited composition range. To cover the full composition range of the Ni-Al binary phase diagram (especially the high-temperature equilibrium phase), multiple sets of experiments are required, also resulting in low efficiency and high cost.

[0004] Furthermore, due to Al's low melting point (933 K), when studying the interdiffusion between pure Ni and pure Al at high temperatures (e.g., >1300 K), Al is in a molten state, making it difficult to prepare and maintain interfacial stability using traditional solid-state diffusion couples. Therefore, developing a high-throughput experimental method capable of obtaining high-temperature phases across the entire composition range in a single operation and effectively studying their phase transitions and diffusion kinetics is of great value. Summary of the Invention

[0005] To address the problems of existing technologies, specifically the difficulty in efficiently obtaining the full-composition range of high-temperature equilibrium phases and their diffusion kinetic parameters in a single experiment for the Ni-Al binary system, and the challenge of conducting stable diffusion couple experiments between pure Ni and liquid Al, this invention provides a high-throughput Ni-Al solid-liquid diffusion couple and its preparation and analysis method. This method, through a specially designed diffusion couple structure, achieves stable interdiffusion between pure Ni and liquid Al at high temperatures. A single experiment can obtain the entire high-temperature phase sequence from the Ni-rich side to the Al-rich side, and accurately analyze phase transition behavior and calculate the diffusion kinetic parameters of each phase.

[0006] To achieve the above-mentioned objectives, the present invention adopts the following technical solution: A high-throughput Ni-Al solid-liquid diffusion couple, characterized in that it comprises: (1) Nickel sleeve; (2) An aluminum block, wherein the aluminum block is interference-fitted into the internal cavity of the nickel sleeve; (3) Nickel end caps, which are sealed and welded to both ends of the nickel sleeve, so that the aluminum block is sealed in a closed cavity formed by the nickel sleeve and the nickel end caps.

[0007] This invention relates to a solid-liquid diffusion couple for studying the phase transition and diffusion kinetics of the Ni-Al system. The diffusion couple is a sealed structure comprising a hollow sleeve made of high-purity nickel with a purity of not less than 99.99%; a high-purity aluminum block with a purity of not less than 99.99% placed inside the sleeve, the aluminum block being press-fitted to the inner wall of the sleeve; and two caps made of high-purity nickel, respectively sealed and welded to the upper and lower ends of the sleeve. The sleeve, aluminum block, and caps together form a sealed cavity used to confine molten aluminum during high-temperature heat treatment and to facilitate solid-liquid interdiffusion with solid nickel, thus enabling the study of the phase transition and diffusion kinetics of the Ni-Al system.

[0008] A method for preparing a high-throughput Ni-Al solid-liquid diffusion couple according to the present invention includes the following steps: ① Component processing and treatment: Nickel sleeves, aluminum blocks and nickel end caps are processed separately, and the contact surfaces of each component are polished, cleaned and acid-washed for activation. ② Assembly: The aluminum block is pressed into the internal cavity of the nickel sleeve in a liquid medium to form an interference fit pre-assembled body; ③ Vacuum sealing welding: The nickel end caps are placed at both ends of the nickel sleeve, and electron beam welding is used in a vacuum environment to seal and weld the nickel end caps to the nickel sleeve, thereby obtaining the high-throughput Ni-Al solid-liquid diffusion couple.

[0009] Preferably, in step ②, the liquid medium is anhydrous ethanol.

[0010] Preferably, in step ③, the vacuum level of the vacuum environment is not less than 1×10⁻ 2 Pa.

[0011] Preferably, during the preparation of the diffusion couple, high-purity Ni rods and Al rods are cut by electrical discharge machining to obtain a sleeve, an aluminum block, and a cap assembly; the surfaces of each assembly are polished, ultrasonically cleaned, and acid-washed for activation; the aluminum block is pressed into the nickel sleeve in an anhydrous ethanol environment to achieve an interference fit; two nickel caps are placed at both ends of the sleeve and sealed by electron beam welding in a vacuum environment.

[0012] A method for studying phase transition and diffusion kinetics of the Ni-Al system using the high-throughput Ni-Al solid-liquid diffusion couple described in this invention includes the following steps: a. Place the encapsulated high-throughput Ni-Al solid-liquid diffusion couple in a heat treatment furnace and anneal it in a temperature range of 1373-1423 K to melt the aluminum block and allow solid-liquid interdiffusion with the nickel sleeve. b. After the annealing process, the diffusion couple is quenched to preserve the microstructure after high-temperature diffusion; c. The quenched sample was cross-sectioned and analyzed. Through a single experiment, multilayer intermetallic compounds and solid solution phases formed according to the composition gradient were obtained at the nickel-aluminum interface.

[0013] Preferably, in step a, the annealing process takes 12-48 hours.

[0014] Preferably, in step c, the multilayer structure includes a γ-Ni(Al) solid solution phase, a γ′-Ni3Al phase, a β′-NiAl phase, a nickel-rich β-NiAl phase, and a β-NiAl phase formed sequentially from the nickel side to the aluminum side.

[0015] Preferably, in step c, the composition range of the β (B2) → β′ (L10) martensitic phase transformation is determined to be 65 at.% Ni to 68 at.% Ni through the analysis.

[0016] Preferably, the analysis in step c includes measuring the thickness of each diffusion layer and calculating the interdiffusion coefficient of each phase in the multilayer structure based on the relationship between the thickness data and the annealing time.

[0017] Preferably, the method for studying the phase transition and diffusion kinetics of the Ni-Al system described in this invention calculates the diffusion activation energy of each phase in the temperature range of 1373-1423 K based on the interdiffusion coefficient at different temperatures using the Arrhenius formula. Q ) and frequency factor ( D 0).

[0018] During the heat treatment process, the sealed diffusion couple sample is placed in a quartz tube filled with inert protective gas and subjected to high-temperature annealing in a muffle furnace. The annealing temperature is above the melting point of Al and below the melting point of Ni, preferably 1373-1423 K, and the annealing time is 12 to 48 h. After the heat treatment, rapid quenching and cooling are performed to retain the high-temperature phase structure.

[0019] Sample preparation and analysis: The cross-section of the diffusion couple was cut, and the cross-section was ground, polished and etched to prepare metallographic samples.

[0020] During the microstructure and composition analysis: the morphology of the diffusion layer was observed using a scanning electron microscope (SEM); and compositional line scanning was performed using an electron probe microanalyzer (EPMA) to determine the compositional gradient and phase composition of each diffusion layer.

[0021] During the phase structure identification process, focused ion beam (FIB) technology was used to prepare transmission electron microscope (TEM) samples in specific phase regions. Bright-field images and selected area electron diffraction (SID) techniques of the TEM were then used to identify the crystal structure, order type, and orientation relationship of each phase.

[0022] During the diffusion kinetics analysis, image analysis software was used to measure the average thickness of each diffusion layer at different annealing times; a linear relationship between the diffusion layer thickness and the square root of the annealing time was established, and the interdiffusion coefficient of each phase at the corresponding temperature was calculated according to the parabolic growth law; combined with the diffusion coefficients at different temperatures, the diffusion activation energy and frequency factor of each phase were calculated using the Arrhenius formula.

[0023] Compared with the prior art, the present invention has the following obvious and prominent substantive features and significant advantages: 1. High throughput advantage: This invention can form a continuous composition gradient from pure Ni to pure Al in a single experiment in a Ni-Al diffusion couple, and obtain all the high-temperature equilibrium phases of the Ni-Al binary phase diagram at the corresponding temperature in one go, including γ-Ni(Al) solid solution, γ′-Ni3Al, β′-NiAl (martensite), Ni-rich β-NiAl phase and β-NiAl phase, which greatly improves experimental efficiency.

[0024] 2. Structural innovation to achieve solid-liquid diffusion: This invention effectively constrains the expansion of molten Al at high temperatures and prevents its loss through a sealing design of "nickel sleeve + nickel cap". This ensures close contact and stable diffusion between pure Ni and liquid Al at high temperatures, solving the technical problem of studying the interdiffusion of pure metal Ni-Al at high temperatures.

[0025] 3. Revealing the complete phase transformation sequence and details: This invention can not only observe conventional diffusion layers, but also clarify the precise compositional range of the β → β′ martensitic phase transformation (e.g., 65-68 at.% Ni), and can directly observe substructures such as martensitic twins through TEM, providing direct evidence for understanding the phase transformation behavior of coatings in thermal cycling.

[0026] 4. Obtaining kinetic parameters of continuous composition regions: Traditional methods typically target single stoichiometric compositions. The method of this invention can distinguish and calculate diffusion kinetic parameters of different composition intervals (Ni-rich β phase and β phase) within the phase region, more accurately reflecting the impact of continuous compositional changes on diffusion within the actual coating / substrate interdiffusion region, and providing data with greater engineering guidance value.

[0027] 5. It has both basic research and engineering application value: The diffusion kinetic parameters (activation energy, diffusion coefficient) obtained by this invention can be directly used to predict the growth of the interdiffusion zone and the degradation rate of the adhesive layer in the thermal barrier coating system, providing key inputs for lifetime prediction models, and providing experimental basis for controlling the diffusion rate and optimizing coating performance through composition design (such as adding elements such as Pt and Cr). Attached Figure Description

[0028] Figure 1 This is a schematic diagram of the Ni-Al solid-liquid diffusion couple in a preferred embodiment of the present invention. The dimensions shown in the diagram are in mm. These dimensions are not intended to limit the assembly structure of the Ni-Al solid-liquid diffusion couple of the present invention. The present invention is not limited to the dimensions shown in the diagram; the required dimensions can be selected and set according to experimental needs.

[0029] Figure 2 The secondary electron image and EPMA composition line scan curve of the diffusion couple cross section after annealing at 1423 K are shown in the preferred embodiment of the present invention.

[0030] Figure 3 The TEM bright-field images and selected area electron diffraction patterns of γ′-Ni3Al, β′-NiAl, β-NiAl and Ni-rich β phases are shown in the preferred embodiments of the present invention.

[0031] Figure 4 This is a graph showing the relationship between the thickness of the diffusion layer and the annealing time and its square root in a preferred embodiment of the present invention. Detailed Implementation

[0032] A preferred embodiment of the present invention provides a high-throughput Ni-Al solid-liquid diffusion couple, comprising: (1) Nickel sleeve; (2) An aluminum block, wherein the aluminum block is interference-fitted into the internal cavity of the nickel sleeve; (3) Nickel end caps, which are sealed and welded to both ends of the nickel sleeve, so that the aluminum block is sealed in a closed cavity formed by the nickel sleeve and the nickel end caps.

[0033] A method for preparing a high-throughput Ni-Al solid-liquid diffusion couple according to a preferred embodiment of the present invention includes the following steps: ① Component processing and treatment: Nickel sleeves, aluminum blocks and nickel end caps are processed separately, and the contact surfaces of each component are polished, cleaned and acid-washed for activation. ② Assembly: The aluminum block is pressed into the internal cavity of the nickel sleeve in a liquid medium to form an interference fit pre-assembled body; ③ Vacuum sealing welding: The nickel end caps are placed at both ends of the nickel sleeve, and electron beam welding is used in a vacuum environment to seal and weld the nickel end caps to the nickel sleeve, thereby obtaining the high-throughput Ni-Al solid-liquid diffusion couple.

[0034] In step ②, the liquid medium is anhydrous ethanol.

[0035] In step ③, the vacuum level of the vacuum environment is not less than 1×10⁻ 2 Pa.

[0036] A method for studying the phase transition and diffusion kinetics of the Ni-Al system using the high-throughput Ni-Al solid-liquid diffusion couple described in a preferred embodiment of the present invention includes the following steps: a. Place the encapsulated high-throughput Ni-Al solid-liquid diffusion couple in a heat treatment furnace and anneal it in a temperature range of 1373-1423 K to melt the aluminum block and allow solid-liquid interdiffusion with the nickel sleeve. b. After the annealing process, the diffusion couple is quenched to preserve the microstructure after high-temperature diffusion; c. The quenched sample was cross-sectioned and analyzed. Through a single experiment, multilayer intermetallic compounds and solid solution phases formed according to the composition gradient were obtained at the nickel-aluminum interface.

[0037] In step a, the annealing process takes 12-48 hours.

[0038] In step c, the multilayer structure includes a γ-Ni(Al) solid solution phase, a γ′-Ni3Al phase, a β′-NiAl phase, a nickel-rich β-NiAl phase, and a β-NiAl phase formed sequentially from the nickel side to the aluminum side.

[0039] In step c, the analysis determines that the composition range of the β (B2) → β′ (L10) martensitic phase transformation is 65 at.% Ni to 68 at.% Ni.

[0040] The analysis in step c includes measuring the thickness of each diffusion layer and calculating the interdiffusion coefficient of each phase in the multilayer structure based on the relationship between the thickness data and the annealing time.

[0041] Based on the interdiffusion coefficients at different temperatures, the diffusion activation energy of each phase in the temperature range of 1373-1423 K was calculated using the Arrhenius formula. Q ) and frequency factor ( D 0).

[0042] The above solution will be further described below with reference to specific embodiments. The preferred embodiments of the present invention are described in detail below: Example

[0043] I. Preparation of diffusion couples: 1. Materials: Ni rods with a purity of 99.99% and Al rods with a purity of 99.999% are selected.

[0044] 2. Machining: The Ni rod is machined into a sleeve with an outer diameter of 10 mm, an inner diameter of 6 mm, and a height of 10 mm using wire electrical discharge machining, as well as an Al column with a diameter of 5.9 mm and a height of 8 mm (achieving an interference fit of 0.1 mm), and two Ni caps for sealing.

[0045] 3. Cleaning: All components were sanded with 2000# SiC sandpaper, ultrasonically cleaned in acetone for 15 min, then acid-washed with 10 vol.% HCl solution for 10 seconds to remove the oxide film, rinsed with alcohol and dried.

[0046] 4. Assembly and Welding: In anhydrous ethanol, press the Al column into the Ni sleeve. Align the upper and lower Ni caps with both ends of the sleeve and place it in the vacuum chamber of an electron beam welder. The vacuum level should be better than 1×10⁻⁻⁻⁻⁶. 2 Under Pa conditions, circumferential welding is performed to form a completely sealed diffusion couple, such as... Figure 1 As shown.

[0047] II. Heat Treatment: (1) Seal the welded diffusion couple sample into a quartz tube that has been evacuated and filled with high-purity argon gas.

[0048] (2) The quartz tube was placed in a muffle furnace and subjected to two heat treatments: the first group was annealed at 1373 K for 12 h, 24 h, 36 h and 48 h respectively; the second group was annealed at 1423 K for 12 h, 24 h, 36 h and 48 h respectively.

[0049] (3) After each heat treatment cycle, the quartz tube is quickly broken and the sample is quenched in water to preserve the high-temperature structure.

[0050] III. Sample Preparation and Analysis: a. Cut the sample perpendicular to the diffusion direction (i.e., the sample cross-section) using a wire cutter.

[0051] b. After mounting, grinding, and polishing, the cut surface is etched with a 5 vol.% HF + 10 vol.% HCl aqueous solution to expose the microstructure.

[0052] c. The interface morphology was observed using a LEO Gemini 1530 scanning electron microscope.

[0053] d. Compositional gradients were analyzed by scanning the compositional lines using a Shimadzu 1720 electron probe with a step size of 1 μm.

[0054] IV. Phase Structure Identification: Based on SEM and EPMA results, cross-sectional TEM thin films were prepared in specific phase regions using focused ion beams.

[0055] Bright-field imaging and selected-area electron diffraction analysis were performed using a FEI Tecnai G2 transmission electron microscope at 200 kV.

[0056] V. Diffusion kinetics calculations: Using Image Pro image analysis software, the thickness of each phase layer at different locations of each sample was measured at least 10 times, and the average value was taken as the layer thickness (Δ) at that annealing time. x ).

[0057] With layer thickness Δ x Plotting Δ on the ordinate and annealing time t on the abscissa verifies that it conforms to a parabolic growth law: x ²∝ t.

[0058] With layer thickness Δ x The vertical axis represents the square root of time. t 1 / 2 Plot the x-axis and perform a linear fit on the data; the slope is... D .

[0059] According to the formula (in D (where interdiffusion coefficient is the interdiffusion coefficient), calculate the diffusion coefficients of each phase at 1373 and 1423 K. D 1 and D 2.

[0060] According to the Arrhenius formula D =D 0 exp( -Q / RT Substitute the values ​​at the two temperatures. D Value, calculate frequency factor D 0 and diffusion activation energy Q .in R The gas constant is T This refers to absolute temperature.

[0061] Analysis of experimental results: Using the methods described above, a complete diffusion layer sequence from the Ni side to the Al side was successfully obtained in a single sample (see appendix). Figure 2 EPMA analysis confirmed that the composition of each layer was in high agreement with the phase diagram. TEM samples were successfully prepared using FIB, and bright-field TEM imaging of the γ′-Ni3Al, β′-NiAl, Ni-rich β-NiAl phases, and β-NiAl phases was obtained (see appendix). Figure 3 TEM analysis confirmed the L12 ordered structure of γ′-Ni3Al (a, d, e), with a = 0.357 nm (see appendix). Figure 3 b), L10 ordered structure of β′-NiAl martensite, a = 0.381 nm, c = 0.327 nm (see appendix) Figure 3 c) and β-NiAl has a B2 ordered structure, a = 0.289 nm (see Appendix). Figure 3 f) The relationship between diffusion layer thickness and time (see appendix) Figure 4 ).

[0062] Conclusion: The high-throughput Ni-Al solid-liquid diffusion couple preparation and analysis method provided by this invention effectively overcomes the limitations of traditional methods. It can efficiently and comprehensively study the phase composition, phase transformation behavior and interdiffusion kinetics of the Ni-Al system at high temperatures, providing a powerful experimental tool and data support for the research and development and life assessment of high-temperature coating materials.

[0063] This invention relates to a high-throughput Ni-Al solid-liquid diffusion couple and its application in the study of material phase transitions and diffusion kinetics. The diffusion couple comprises a nickel sleeve, an aluminum block encapsulated inside the sleeve, and nickel end caps sealed and welded to both ends of the sleeve. The preparation method includes: surface pretreatment of the nickel sleeve, aluminum block, and nickel end caps to achieve a tight interference fit; and sealing welding of the nickel end caps to the sleeve using electron beam welding technology in a vacuum environment to form a sealed cavity with an internal vacuum or inert atmosphere. In application, the encapsulated diffusion couple is annealed in the temperature range of 1373-1423 K, utilizing the melting of aluminum to achieve solid-liquid interdiffusion, followed by quenching to retain the high-temperature microstructure. The core of this invention lies in achieving solid-liquid contact and interdiffusion between pure nickel and pure aluminum at high temperatures through a unique mechanical encapsulation and vacuum sealing design, overcoming the drawbacks of traditional solid-state diffusion couples that cannot cover the full composition range and require multiple sets of experiments. This invention provides an efficient and comprehensive method for studying the formation mechanism and diffusion behavior of high-temperature phases in materials. It is particularly suitable for the development and failure mechanism analysis of nickel-aluminum based adhesive layer materials for thermal barrier coatings, and has important scientific and engineering application value. A single experiment can obtain the multilayer structure of all high-temperature equilibrium phases and determine key kinetic parameters such as the interdiffusion coefficient, frequency factor and diffusion activation energy of each phase in a specific temperature range.

[0064] The embodiments of the present invention have been described above in conjunction with the accompanying drawings. However, the present invention is not limited to the above embodiments. Various changes can be made according to the inventive purpose of the present invention. Any changes, modifications, substitutions, combinations or simplifications made in accordance with the spirit and principle of the technical solution of the present invention shall be equivalent substitutions. As long as they meet the inventive purpose of the present invention and do not deviate from the technical principle and inventive concept of the present invention, they shall fall within the protection scope of the present invention.

Claims

1. A high-throughput Ni-Al solid-liquid diffusion couple, characterized in that, include: (1) Nickel sleeve; (2) An aluminum block, wherein the aluminum block is interference-fitted into the internal cavity of the nickel sleeve; (3) Nickel end caps, which are sealed and welded to both ends of the nickel sleeve, so that the aluminum block is sealed in a closed cavity formed by the nickel sleeve and the nickel end caps.

2. A method for preparing a high-throughput Ni-Al solid-liquid diffusion couple as described in claim 1, characterized in that, Includes the following steps: ① Component processing and treatment: Nickel sleeves, aluminum blocks and nickel end caps are processed separately, and the contact surfaces of each component are polished, cleaned and acid-washed for activation. ② Assembly: The aluminum block is pressed into the internal cavity of the nickel sleeve in a liquid medium to form an interference fit pre-assembled body; ③ Vacuum sealing welding: The nickel end caps are placed at both ends of the nickel sleeve, and electron beam welding is used in a vacuum environment to seal and weld the nickel end caps to the nickel sleeve, thereby obtaining the high-throughput Ni-Al solid-liquid diffusion couple.

3. The method for preparing a high-throughput Ni-Al solid-liquid diffusion couple according to claim 2, characterized in that, In step ②, the liquid medium is anhydrous ethanol.

4. The method for preparing a high-throughput Ni-Al solid-liquid diffusion couple according to claim 2, characterized in that, In step ③, the vacuum level of the vacuum environment is not less than 1×10⁻ 2 Pa.

5. A method for studying the phase transition and diffusion kinetics of the Ni-Al system using the high-throughput Ni-Al solid-liquid diffusion couple described in claim 1, characterized in that, Includes the following steps: a. Place the encapsulated high-throughput Ni-Al solid-liquid diffusion couple in a heat treatment furnace and anneal it in a temperature range of 1373-1423 K to melt the aluminum block and allow solid-liquid interdiffusion with the nickel sleeve. b. After the annealing process, the diffusion couple is quenched to preserve the microstructure after high-temperature diffusion; c. The quenched sample was cross-sectioned and analyzed. Through a single experiment, multilayer intermetallic compounds and solid solution phases formed according to the composition gradient were obtained at the nickel-aluminum interface.

6. The method for studying phase transition and diffusion kinetics of the Ni-Al system according to claim 5, characterized in that, In step a, the annealing process takes 12-48 hours.

7. The method for studying phase transition and diffusion kinetics of the Ni-Al system according to claim 5, characterized in that, In step c, the multilayer structure includes a γ-Ni(Al) solid solution phase, a γ′-Ni3Al phase, a β′-NiAl phase, a Ni-rich β phase, and a β-NiAl phase formed sequentially from the nickel side to the aluminum side.

8. The method for studying phase transition and diffusion kinetics of the Ni-Al system according to claim 5, characterized in that, In step c, the analysis determines that the composition range of the β (B2) → β′ (L10) martensitic phase transformation is 65 at.% Ni to 68 at.% Ni.

9. The method for studying phase transition and diffusion kinetics of the Ni-Al system according to claim 5, characterized in that, The analysis in step c includes measuring the thickness of each diffusion layer and calculating the interdiffusion coefficient of each phase in the multilayer structure based on the relationship between the thickness data and the annealing time.

10. The method for studying phase transition and diffusion kinetics of the Ni-Al system according to claim 5, characterized in that, Based on the interdiffusion coefficients at different temperatures, the diffusion activation energy of each phase in the temperature range of 1373-1423 K was calculated using the Arrhenius formula. Q ) and frequency factor ( D 0).